Systematics, morphometry, and distribution of Eptesicus fuscus miradorensis (H. Allen, 1866) (Chiroptera: Vespertilionidae), with notes on baculum morphology and natural history - Ramírez-Chaves, Héctor E.; Alarcón Cifuentes, Mallerly; Noguera-Urbano, Elkin A; Pérez, Weimar A; Torres-Martínez, Maria M; Ossa-López, Paula A.; Rivera-Páez, Fredy A.; Morales-Martínez, Darwin Manuel (THERYA, 2023)
The brown bat Eptesicus fuscus (Chiroptera: Vespertilionidae) is a widely distributed species with up to 11 subspecies ranging from North America, some Caribbean islands, and Central and northern South America. Within the species, Eptesicus fuscus miradorensis occurs from North America to South America being the only subspecies that occurs in the continental area of the Neotropical region and might be considered a full species. Also, it has been suggested that E. f. miradorensis shows a clinal morphologic variation from the northernmost populations of Central America toward South America. We evaluated the systematic position of E. f. miradorensis using genetic samples from Central and South America. In addition, we assessed the morphometric variations of E. f. miradorensis using 14 external and cranial measurements of specimens distributed along America. To evaluate the clinal variation and interspecific changes through its distribution, we assigned three groups considering the localities of origin i) North (México), ii) Center (Guatemala-Panamá), and iii) South (Colombia-Venezuela) using multivariate analyzes. We also compiled the localities of the revised specimens and these from databases to determine the environmental factors that potentially constrain the distribution of the taxon. We suggest that E. f. miradorensis should be elevated to the species level based on genetic comparisons. Additionally, we did not find sexual dimorphism or size variation associated with its distribution. The species is distributed from México to South America (Colombia, Venezuela, and Ecuador) in elevations that average over 1,000 m, showing a strong association with high mountain ecosystems. This taxon increases to 12 the number of species of bats of the subgenus Eptesicus in South America.